A Conceptual Model of Engagement Profiles Throughout the Decades of Older Adulthood - Carr, Kelly; Weir, Patti (Frontiers in Psychology, 2019)
Engagement with life is essential to successful aging. This study explored ‘how’ and ‘why’ engagement profiles change throughout older adulthood using a mixed methods design. Fifty-four participants (mean age = 79.17 years, age range = 65-97 years; 21 males, 33 females) completed questionnaires to quantify ‘past’ and ‘present’ engagement. Focus groups and semi-structured interviews were completed with a subsample of participants (n = 42). Participation in productive and active leisure activities decreased with increasing age, while social and passive leisure engagement remained stable. Changes in engagement were a function of five themes derived from the fundamental qualitative description: (a) health and physical limitations, (b) death, (c) freedom, (d) desire, and (e) external influential factors. This study highlights the importance of engagement to successful aging and has practical implications for practitioners.